PENERAPAN MODEL PMBELAJARAN WRITING PICTURE UNTUK MNINGKATKAN KEMAMPUAN MENULIS KARANGAN PERSUASI SISWA KELAS IV DI SD NEGERI MINASA UPA KOTA MAKASSAR - Dwi Suci Rahmadani; Andi Adam; Desy Ayu Andhira (STKIP Subang, 2025)
This study aims to improve the persuasive writing skills of fourth-grade students at Minasa Upa State Elementary School in Makassar City through the Writing Picture learning model. The underlying problem is students' low persuasive writing skills, characterized by difficulty expressing ideas, constructing logical arguments, inappropriate word choice, and a lack of compelling, persuasive writing. The Writing Picture learning model was implemented as an effort to help students develop ideas through visual media, thus facilitating their ability to express their thoughts in writing with an appropriate composition structure. The study was conducted as a classroom action research (CAR). The subjects were 25 fourth-grade students at Minasa Upa State Elementary School in Makassar City. Data collection techniques included observation, testing (evaluation), and documentation. The results of the study indicate that the application of the Writing Picture learning model improved students' persuasive writing skills. The average student score increased from 61.6 in cycle I to 90.6 in cycle II. Furthermore, students' learning completion also increased from 40% to 100%.